An assessment of teacher's opinions on the meeting level of the social needs of the social studies curriculum (sample of Diyarbakır city) - Gömleksiz, Mehmet Nuri; Cüro, Elif (My University, 2011)
The aim of this study is to assess both classroom teachers' and social studies teachers' opinions on the meeting level of the social needs of the social studies curriculum. The study was conducted on totally 775 teachers including 631 classroom teachers and 144 social studies teachers who worked in 94 public primary schools in Diyarbaki{dotless}r city centre in 2007-2008 academic year. The data of the study were collected by using a 5-point 21-item Likert type scale. The statements were first piloted using a sample of 104 teachers for reliability and validity analyses. Cronbach Alpha of the scale was found to be 0.957. KMO value was measured to be 0.958 and Bartlett's test was calculated to be 12638,030. Results were analyzed in terms of seniority, branch and school's socio-economic level. One way ANOVA, independent group t test, KWH, MWU and LSD tests were used to analyze the data. The teachers who were new at teaching profession found the social studies curriculum more effective than more experienced ones. Social studies teachers found the curriculum more effective than the 4th and 5th grade classroom teachers. No statistically significant differences were found among the groups in terms of school's socio-economic level. The teachers should have in-service seminars to implement social studies curriculum effectively. Schools are offered to meet the required physical equipment.
Sosyal bilgiler dersi ö?retim programinin toplumsal ihtiyaçlari karşilama düzeyine ilişkin ö?retmen görüsleri (Diyarbakir ili örne?i)
Keywords: Classroom teacher; Social needs; Social studies curriculum; Social studies teacher